2023
DOI: 10.30630/joiv.7.1.1644
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management Factors and Its Impact on Organizational Performance: A Systematic Literature Review

Abstract: Knowledge management can help organizations to improve their performance. Many studies show that knowledge management impacts organizational performance. Human capital is considered a mediating role in knowledge management's impact on organizational performance, but it is still blurred, and only a few studies are related to this issue. Moreover, various factors influence knowledge management, such as organizational structure, culture, technology, strategy, trust, and leadership, but maybe other factors have no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…An example is the application of an open communication culture where every employee in any position can express their opinions and be able to provide input to related sections. These results are also in line with previous research journals from (Darmawan et al, 2023) in his research entitled "Knowledge Management Factors and Its Impact on Organizational Performance". which concluded that "Eight factors directly affect the implementation of Knowledge Management: organizational structure, culture, leadership, human resource practices, human behavior, trust, technology, and strategy, which can improve organizational performance".…”
Section: Factors Affecting Knowledge Management and Its Effect On Org...supporting
confidence: 92%
See 2 more Smart Citations
“…An example is the application of an open communication culture where every employee in any position can express their opinions and be able to provide input to related sections. These results are also in line with previous research journals from (Darmawan et al, 2023) in his research entitled "Knowledge Management Factors and Its Impact on Organizational Performance". which concluded that "Eight factors directly affect the implementation of Knowledge Management: organizational structure, culture, leadership, human resource practices, human behavior, trust, technology, and strategy, which can improve organizational performance".…”
Section: Factors Affecting Knowledge Management and Its Effect On Org...supporting
confidence: 92%
“…Based on the results of the analysis, it shows that the influence between Organizational Structure on Knowledge Management is significant. With a significant influence between organizational structure and knowledge management in this study, it shows that an organizational structure that is flexible, open, and supports effective communication, good coordination, and easy knowledge exchange in these Korean multinational companies, can improve the application of knowledge management that is currently implemented, (Darmawan et al, 2023) in his research entitled "Knowledge Management Factors and Its Impact on Organizational Performance". which concluded that "Eight factors directly affect the implementation of Knowledge Management: organizational structure, culture, leadership, human resource practices, human behavior, trust, technology, and strategy, which can improve organizational performance".…”
Section: Factors Affecting Knowledge Management and Its Effect On Org...mentioning
confidence: 75%
See 1 more Smart Citation
“…Previous research has found that combining augmented reality technology with educational content provides effectiveness and appeal to teaching and learning for students in the real world [14]. Augmented Reality offers unique affordability by combining the physical and virtual worlds with continuous user control from a vantage point and interactivity [15].…”
Section: Introductionmentioning
confidence: 99%